Forest law enforcement and offences in the state of Perak, peninsular - Baharom, Nor Azmi; Hassan Zaki, Pakhriazad; Ismail, Mohd Hasmadi; Bawon, Paiman (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
The forestry sector is undergoing substantial policy change in response to broader developments such as economic growth, globalization of economic, privatization and trade liberalization. Forest law enforcement is a critical part of forest management since it directs the relationship between many parties, particularly timber companies, with the forest asset. The objective of the study was to identify the awareness of forest law enforcement and offences in the state of Perak. The research was conducted with a questionnaire survey with 5-point Likert type answering options among 400 local respondents from ten mukims namely Pengkalan Hulu, Belukar Semang, Gerik, Belum, Kenering, Kerunai, Temenggor, Lenggong, Durian Pipit and Temelong. Mean perception score was 3.126 which indicated respondents agreed with the awareness forest law and offences issues. The SPSS shows the perception score significantly differed among different age groups, however there was no difference of perceptions among other variables such as race, religion or education level. The study concluded that regardless of socio-economic factors the respondents have concurred with the situation of awareness on forest law enforcement in the studied mukims.